PSYCHOANALYTICAL INQUIRES ON MUSIC. GUSTAV MAHLER’S ORCHESTRAL SONGS (Mūzikas akadēmijas raksti, 2024)
Psychoanalysis represented a turning point in science, being also the origin for some of the most controversial ideological changes at the late 19th century. Its father, Sigmund Freud, was not satisfied with the therapeutic practice, applying it instead to various products of human thinking and spirit, such as literature, painting or sculpture. Although much later and with many more difficulties, music also became an instrument used by some psychoanalysts to verify their theories. Together with Ludwig van Beethoven and Wolfgang Amadeus Mozart, Gustav Mahler is one of the most analyzed composers in the history of music. The notes he wrote on his manuscripts, rich in extramusical meanings, allowed the clinicians and musicologists to analyze both the man and the musician. The controversies built around his personality reached a level almost without precedent. The permanent conflict that one can feel in Mahler’s music has been explained in terms of the struggle between his activity as a conductor and the necessity for creation. Furthermore, his music reflects the turbulent socialcultural environment typical for the last days of the AustroHungarian Empire, as well as the tensions of his childhood and youth.